Propuesta de un programa educativo para el manejo de efectos secundarios por citostaticos en el Hospital Oncológico "Wilson Franco Cruz" de la ciudad de Machala de julio a septiembre del 2012. - Suconota Pintado, Ana (2015)
Presented side effects are very important to study and prevention ranging from somatic complaints to genetic, failure to observe technical-protocols is considered the study whose general objective: To propose an educational program on managing side effects of cytostatic directed staff Cancer hospital to improve level of knowledge. July to September 2012; Using a descriptive study, observational, cross-epidemiological cohort cleared variables: knowledge, compliance and side effects; working with a universe of 42 people, data were raised using observation guide-survey to measure knowledge before and after the intervention, the most significant results: 42.86% of the staff previously applied biosafety standards, the level of knowledge was 52.38%: after the intervention applying biosafety standards increased 100% compliance, knowledge level improved by 90%. EPP uses gloves 85.71% 92.86% management and surgical mask used for handling cytostatics .Presented side effects: 9.52% urticaria- alopecia presented with cyclophosphamide: 4.76% showed alopecia-mucosal irritation-hawking with doxorubicin, it is concluded that the intervention was of great impact, this study suggests that the constant educational intervention is essential prevention.